2012
DOI: 10.4236/ns.2012.428090
|View full text |Cite
|
Sign up to set email alerts
|

Seismic pounding and collapse behavior of neighboring buildings with different natural periods

Abstract: Seismic pounding phenomena, particularly the collision of neighboring buildings under long-period ground motion, are becoming a significant issue in Japan. We focused on a specific apartment structure called the Nuevo Leon buildings in the Tlatelolco district of Mexico City, which consisted of three similar buildings built consecutively with narrow expansion joints between the buildings. Two out of the three buildings collapsed completely in the 1985 Mexican earthquake. Using a finite element code based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This property appears to be problematic for any oncoming intense ground motion.The incremental dynamic analysis has been also applied to check the required reserve capacity of the structure to prevent the collapse of the structure. The results showed that in single seismic events, the examined structures have greater capacity in comparison with the case of seismic sequences, which lead to collapse with smaller values of PGA.Previous works found that the pounding phenomenon can be beneficial in many cases. It should be noted that all previous works examined exclusively regular buildings, and their findings are also confirmed here examining the pounding combination no.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This property appears to be problematic for any oncoming intense ground motion.The incremental dynamic analysis has been also applied to check the required reserve capacity of the structure to prevent the collapse of the structure. The results showed that in single seismic events, the examined structures have greater capacity in comparison with the case of seismic sequences, which lead to collapse with smaller values of PGA.Previous works found that the pounding phenomenon can be beneficial in many cases. It should be noted that all previous works examined exclusively regular buildings, and their findings are also confirmed here examining the pounding combination no.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Isobe et al . examined recently the seismic pounding and collapse behaviour of neighbouring buildings with different natural periods.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis result indicates that the smaller stairway tower is significantly influenced by the pounding while the larger main building is slightly influenced. Isobe et al (2012) successfully simulated the pounding and collapse behaviors of the Nuevo León building using a large 3D numerical mode, although the change of natural period during the vibration is not computed.…”
Section: Introductionmentioning
confidence: 99%
“…Fine 3D numerical models of a large number of degrees of freedom have also been used to estimate impact loads due to tsunami waves (Salem et al 2014) and traffic accidents (Yi et al 2015). Seismic poundings of adjacent buildings have been conducted by scaled model tests (Goland 1955;van Mier et al 1991;Zhu et al 2002;Jankowski 2010) and analytical methods (Anagnostopoulos et al 1992;Maison et al 1992;Davis 1992;Jankowski 2005;Jankowski 2006;Anagnostopoulos et al 2008;Isobe et al 2012). Jankowski conducted a finite element analysis of (Jankowski 2009) the pounding behavior between main building and stairway tower of Olive View Hospital damaged in San Fernando earthquake in 1971.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1985 Mexico Earthquake, a 14-story RC residential building collapsed due to resonance with long-period motion and pounding between neighboring building units (Bertero1986; Isobe et al 2012;Chujo et al 2016). Several analytical investigations have been conducted for this building.…”
Section: Introductionmentioning
confidence: 99%